Analisis Kepemimpinan K.H Wahid Hasyim Terhadap Reformasi Pendidikan Pesantren - M. Taofik Kurohman; Anny Wahyuni; Budi Purnomo (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
K.H. Abdul Wahid Hasyim is one of the founding fathers of the Indonesian nation. His services, thoughts and dedication to Indonesia are unquestionable. With his family background and education, he has a visionary ambition to change the conservative education system in Islamic boarding schools and of course by not abandoning the priority religious education. This paper attempts to describe Wahid Hasyim's biography and examines his various thoughts on education as well as the content of his vision of reforming Islamic boarding school education. The method used in this study is the historical method with the following steps: heuristics, verification, interpretation and historiography. From this research, it was found that (1) The life journey of K.H. Abdul Wahid Hashim. (2) The way K.H. Abdul Wahid Hasyim in leading (3) Thoughts of K.H. Abdul Wahid Hasyim towards the reform of pesantren education.